2012
DOI: 10.1038/jhh.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their tissue inhibitors in hypertension-related pregnancy complications

Abstract: Matrix metalloproteinases (MMPs) are a family of endopeptidases that degrade the components of the extracellular matrix (ECM) such as collagen, and thus contribute to the remodelling and the physiological homeostasis of the ECM and its blood supply. The activities of these enzymes are regulated by endogenous tissue inhibitors of metalloproteinases (TIMPs), and it has been suggested that a balance between MMPs and TIMPs plays an important role in vascular remodelling, angiogenesis and vasodilatation in a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 103 publications
(51 reference statements)
0
29
0
1
Order By: Relevance
“…15 The matrix metalloproteinase (MMP) system has been a suggested mechanism for the remodeling of systemic arteries during pregnancy. 16 Circulating MMP-9 levels are higher in normal pregnancy as compared non-pregnant women. 17 In women with pregnancy induced hypertension, MMP-9 levels are raised, but the circulating levels of tissue inhibitors of metalloproteinases (TIMP-1 and TIMP-2) are also raised.…”
Section: Discussionmentioning
confidence: 98%
“…15 The matrix metalloproteinase (MMP) system has been a suggested mechanism for the remodeling of systemic arteries during pregnancy. 16 Circulating MMP-9 levels are higher in normal pregnancy as compared non-pregnant women. 17 In women with pregnancy induced hypertension, MMP-9 levels are raised, but the circulating levels of tissue inhibitors of metalloproteinases (TIMP-1 and TIMP-2) are also raised.…”
Section: Discussionmentioning
confidence: 98%
“…However, very few of these regulatory factors have been investigated in depth. Recent reports have demonstrated that MMP-9 down-regulation and TIMP-1 up-regulation can both lead to reduced trophoblast invasiveness [15,16,17]. We have also investigated the roles of MMP-9 and TIMP-1 in trophoblast invasion.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 and TIMP-1 are both closely associated with trophoblast invasion. Down-regulation of MMP-9 and up-regulation of TIMP-1 may both lead to decreased trophoblast invasion [16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…They often bind with heparin sulphate glycosaminoglycans on the cell surface and have wide range of substrates [11]. …”
Section: Reviewmentioning
confidence: 99%